The impact of internet use on rural household energy transition: moderating effect based on social interaction - Gao, Jingyu; Zhou, Jing; Liu, Yunru (Frontiers in Energy Research, 2023)
Household energy transition is the key to changing and upgrading China's energy consumption pattern. Directly using traditional biomass fuels is not only one of the reasons why the opportunity between urban and rural areas is inequality but also a critical symbol of the inequality of energy consumption within rural areas. This study investigates the association between two information acquisition mechanisms, namely Internet use and social interaction, and rural household energy transition, using the Chinese General Social Survey in the year 2015 (CGSS 2015). After converting the consumption of each fuel to standard coal, according to the energy ladder theory, this study classifies the main types of household energy into three categories: primitive fuels, transition fuels, and advanced fuels. Then this study uses the ordered probit model to empirically analyze 1023 rural household samples in China. The results show that, compared to rural households that never use the Internet, an increase in the frequency of Internet use significantly enhances the probability of rural households using advanced fuels, while decreasing the probability of using primitive and transition fuels simultaneously. However, the effect direction of social interaction works is the opposite of Internet use completely. The intrinsic mechanism result shows that although social interaction reduces the strength of the role of Internet use in rural household energy transition, it has not yet completely offset the positive effect of Internet use on the rural household energy transition. The results of this study provide references for removing the blocking barriers to contact and use of the Internet by rural residents, improving the perceived quality of obtained information through social interaction, and solidly promoting rural energy transition and sustainable development of resources and the environment.